2018
DOI: 10.1108/ijppm-05-2017-0126
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between management characteristics and firm innovation

Abstract: Purpose The purpose of this paper is to assess the relationship between some management features (management capability, management entrenchment, agency costs and overconfidence) and the innovation of companies listed on the Tehran Stock Exchange. Design/methodology/approach The study carried out during 2009–2015. A total of 125 companies were selected from eight industries as the sample of study using the method of systematic elimination. A descriptive-correlational design was used in this study and panel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…The culture of the organization or institution is no less important than the availability of financial resources and technological capabilities of the institution. The movement of the organization is an innovative management that accommodates the variables of the times and is familiar with the modern methods of innovative management, which need to be applied in organizations' basic requirements, to contribute to improve the quality of administrative and internal processes work (Muzamil Naqshbandi and Kaur, 2014).There are a number of administrative requirements that must be met in the regulatory environment of innovative management, summarized in the following as according to (Salehi et al, 2018):…”
Section: Innovative Managementmentioning
confidence: 99%
“…The culture of the organization or institution is no less important than the availability of financial resources and technological capabilities of the institution. The movement of the organization is an innovative management that accommodates the variables of the times and is familiar with the modern methods of innovative management, which need to be applied in organizations' basic requirements, to contribute to improve the quality of administrative and internal processes work (Muzamil Naqshbandi and Kaur, 2014).There are a number of administrative requirements that must be met in the regulatory environment of innovative management, summarized in the following as according to (Salehi et al, 2018):…”
Section: Innovative Managementmentioning
confidence: 99%
“…Furthermore, their findings show that there is a positive and significant relationship between managerial entrenchment and firm innovation. In another investigation, Salehi et al (2018b) investigate the relationship between some management features (management capability, management entrenchment, agency costs and overconfidence) and the innovation of companies listed on the TSE market. The findings of their study explore several views in this line of literature.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In line with Bathula and Singh (2015) who concluded that top management involvement is vital for enhancing high efficiency and success. Similarly, Salehi et al, (2018) also argued that TMC are not only prominent for high profitability but also very crucial for boosting operational activities. Additionally, Zhao, Zha, Hou and Liang (2019) claimed that in emerging economies such as China, the top management team significantly influences operational activities and plays a crucial role in the improvement of firm efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…TMC are the firm-level indicators that affect a firm's performance (Bathula & Singh, 2015). TMC are not only important for the high performance of a firm but also influence innovative and operational activities (Salehi, DashtBayaz, & Moghadam, 2018). Upper Echelon theory suggests that a firm's success and performance are influenced by the top management team rather than bottom or middle-level managers (Hambrick & Mason, 1984;Tseng & Lee, 2014).…”
Section: Top Management Capabilities and Firm's Efficiencymentioning
confidence: 99%